Use of chromatin remodeling ATPases as RNAi targets for parental control of western corn rootworm (Diabrotica virgifera virgifera) and Neotropical brown stink bug (Euschistus heros). (April 2016) - Fishilevich, Elane; Vélez, Ana M.; Khajuria, Chitvan; Frey, Meghan L.F.; Hamm, Ronda L.; Wang, Haichuan; Schulenberg, Greg A.; Bowling, Andrew J.; Pence, Heather E.; Gandra, Premchand; Arora, Kanika; Storer, Nicholas P.; et al.
Abstract: RNA interference (RNAi) is a gene silencing mechanism that is present in animals and plants and is triggered by double stranded RNA (dsRNA) or small interfering RNA (siRNA), depending on the organism. In the western corn rootworm (WCR), Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), RNAi can be achieved by feeding rootworms dsRNA added to artificial diet or plant tissues transformed to express dsRNA. The effect of RNAi depends on the targeted gene function and can range from an absence of phenotypic response to readily apparent responses, including lethality. Furthermore, RNAi can directly affect individuals that consume dsRNA or the effect may be transferred to the next generation. Our previous work described the potential use of genes involved in embryonic development as a parental RNAi technology for the control of WCR. In this study, we describe the use of chromatin-remodeling ATPases as target genes to achieve parental gene silencing in two insect pests, a coleopteran, WCR, and a hemipteran, the Neotropical brown stink bug, Euschistus heros Fabricius (Hemiptera: Pentatomidae). Our results show that dsRNA targeting chromatin-remodeling ATPase transcripts, brahma, mi-2, and iswi strongly reduced the fecundity of the exposed females in both insect species. Additionally, knockdown of chd1 reduced the fecundity of E. heros . Graphical abstract: Highlights: Chromatin remodeling ATPases were identified in the western corn rootworm and the Neotropical brown stink bug. This study is the first demonstration of lethal and parental RNAi responses in pentatomid stink bugs by injection. Knockdown of brahma, mi-2, iswi-1, and iswi-2 decreased the fecundity of WCR. Knockdown of brahma, mi-2, iswi-1, iswi-2, and chd1 decreased the fertility and overall fecundity of Euschistus heros . Chromatin remodeling ATPases are promising gene targets for parental RNAi-based control of multiple pest insects.